Management of Natural Disaster and Its Influence on Economic–Environmental Performance: Fresh Evidence From BRICS - Lu, Fami (Frontiers in Environmental Science, 2022)
Previous literature documented the importance of natural disasters and their impact on economic performance but it ignored the effects on the environment. This study examines the effect of natural disasters on the economic and environmental performance of BRICS economies over the period 1995-2019. The study applies a panel autoregressive distributed lag (ARDL) and panel quantile regression approaches. The empirical findings show that natural disasters decrease economic growth but increase CO2 emissions. The findings of panel quantile regression display a significant negative impact of natural disasters on economic growth from the middle (30th) to higher (80th) quantiles. However, natural disaster significantly increases carbon emissions from the middle (50th) to higher (95th) quantiles. This study suggests the importance of proper planning for the management of natural disasters.